First observation of excited [omega]-b states - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2020)
We report four narrow peaks in the Ξ0bK− mass spectrum obtained using pp collisions at center-of-mass energies of 7, 8, and 13 TeV, corresponding to a total integrated luminosity of 9 fb−1 recorded by the LHCb experiment. Referring to these states by their mass, the mass values are m[Ωb(6316)−]=6315.64±0.31±0.07±0.50 MeV, m[Ωb(6330)−]=6330.30±0.28±0.07±0.50 MeV, m[Ωb(6340)−]=6339.71±0.26±0.05±0.50 MeV, m[Ωb(6350)−]=6349.88±0.35±0.05±0.50 MeV, where the uncertainties are statistical, systematic, and the last is due to the knowledge of the Ξ0b mass. The natural widths of the three lower mass states are consistent with zero, and the 90% confidence-level upper limits are determined to be Γ[Ωb(6316)−]<2.8 MeV, Γ[Ωb(6330)−]<3.1 MeV and Γ[Ωb(6340)−]<1.5 MeV. The natural width of the Ωb(6350)− peak is 1.4+1.0−0.8±0.1 MeV, which is 2.5σ from zero and corresponds to an upper limit of 2.8 MeV. The peaks have local significances ranging from 3.6σ to 7.2σ. After accounting for the look-elsewhere effect, the significances of the Ωb(6316)− and Ωb(6330)− peaks are reduced to 2.1σ and 2.6σ, respectively, while the two higher mass peaks exceed 5σ. The observed peaks are consistent with expectations for excited Ω−b resonances.
Im Titel ist Omega als griechischer Buchstabe dargestellt
Im Titel sind "-" und "b" untereinander geschrieben: "-" hochgestellt, "b" tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, R. Kopecna, B. Leverington, H. Malygina, J. Marks, S. Neubert, A. Piucci, N. Skidmore, U. Uwer, L. Witola, A. Zhelezov [und weitere]
Gesehen am 16.04.2020